علاوة عمارة: بونة والتوجه الساحلي لبلاد كتامة من ق: 3-6هـ/9-12م - بوبيدي حسين (University of Eloued جامعة الوادي, 2024)
This article studies the progressive prosperity of coastal activities in the Kutāma region. The transfer of the political and economic center from the eastern Maghreb to the interior of the country caused an unfavorable situation in the northern regions. It was not until the 11th century that the old trading posts and towns that had not played a significant role in the first century of Islam in the Maghreb were developed. Bône regained its status as a maritime outlet for a vast hinterland. The crisis that hit the hinterland following successive waves of drought and especially the political and social instability caused by the Hilalian presence accelerated the process of coastalization of the Kutāma land. However, Christian raids and the Hilalian push led to a regression of economic activities in the eastern part of the Kutāma land. Benefiting from massive mountain ranges with rugged relief, the western part of the Kutāma region experienced a more significant coastalization. يدرس هذا المقال الازدهار التدريجي الذي عرفته الأنشطة الساحلية في بلاد كتامة، فبعد انتقال الثقل السياسي والاقتصادي لبلاد المغرب الشرقي إلى الداخل منذ الفتوحات الأموية تضررت المناطق الشمالية، التي استعادت منذ القرن 5هـ/11م استغلال الموانئ القديمة ونشطت المدن الساحلية التي توارت إلى الهامش في القرن الهجري الأول، وفي هذا السياق استرجعت بونة دورها كمنفذ بحري لتصدير السلع القادمة من مناطق واسعة في الداخل، وبسبب الأزمات التي ضربت المناطق الداخلية التي عانت من جفاف قاس تسارع ازدهار الأنشطة الساحلية في بلاد كتامة، وقد تعزز ذلك مع الاضطرابات السياسية والاجتماعية التي صاحبت الحضور الهلالي، لكن هذا الازدهار سرعان ما تعرض للضغط الهلالي والهجمات المسيحيىة النورماندية فأدى إلى تراجع الأنشطة الاقتصادية في الجزء الشرقي من بلاد كتامة، أما الجزء الغربي فقد استفاد من طبيعته التضاريسية (وجود سلسلة جبلية ذات تضاريس وعرة) ليقوم بدور تجاري هام على سواحله.
ترجمة من الفرنسية إلى العربية لمقال: Allaoua Amara: Bûna Et La Littoralisation Du Pays Kutāma
Keywords: بونة; كتامة; الأنشطة الساحلية; التجارة; جيجل; Bûna; kutāma; the coastline; commerce; Jijel